Loan Guarantees: An Option Pricing Theory Perspective - Pizzutilo, Fabio; Calò, Francesco (International Journal of Economics and Financial Issues, 2015)
In this paper we analyse security loan guarantees in the light of the option pricing theory. We interpret them as put options on the cash flows of a secured debt. We highlight that the value of the guarantee is always positive before a loan's maturity and it depends on the same factors that determine the value of a financial option. We also analyse their value in the condition of market efficiency and we conclude that the inefficiencies of the financial markets justify their existence. Finally, we focus our attention on public agencies' intervention by offering credit guarantees to private firms. Keywords: Loan guarantee; option pricing theory; public guarantee; guarantee value JEL Classifications: H81